Hubungan antara Keterlibatan Kerja Dengan Rasa Tujuan Hidup Pada Generasi Z Yang Bekerja - Zannethi, Muhamad Bathi; Hutahaean, Erik Saut H.; Muzzamil, Ferdy (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to examine the relationship between work engagement and sense of purpose in life among working Generation Z employees. The background of this research is based on the phenomenon of lack of meaningful work experienced by Generation Z, in which work perceived as lacking meaning can lead to decreased motivation, work engagement, and psychological well-being. This study employed a quantitative method with a correlational design. The participants consisted of 150 working Generation Z employees at PT X, selected based on power analysis calculations. Data were collected using a work engagement scale and a sense of purpose in life scale and analyzed using Pearson’s correlation after meeting the assumptions of normality, linearity, and homogeneity. The results indicated a significant and positive relationship between work engagement and sense of purpose in life (r = 0.813; p 0.001), suggesting that higher levels of work engagement are associated with a stronger sense of purpose in life. The categorization results showed that the majority of respondents were in the high category for both work engagement and sense of purpose in life. These findings highlight that a sense of purpose in life is an important psychological resource in enhancing work engagement among Generation Z. This study provides practical implications for organizations to not only focus on structural aspects of work but also support the development of employees’ sense of meaning and life purpose to improve work engagement and psychological well-being.